Estudios sobre plantas andinas, ii (1941)
Weinmannia penicillata / Weinmannia subvelutina / Weinmannia myrtifolia / Weinmannia sclerophylla / Weinmannia caquetana / Weinmannia microcarpa / Weinmannia parvifoliolata / Weinmannia putumayensis / Weinmannia sibundoya / Weinmannia magnifolia / Weinmannia Duquei